Assessing the threat of terrorist use of chemical, biological, radiological and nuclear weapons in the South-East European countries - Chalaris, Michail; Stavrakakis, P.; Sarafis, Pavlos (My University, 2010)
Many scientists and politics argued that ‘tomorrow’s threat may include the use of chemicals, bacteriological agents, radioactive materials and even nuclear technology. In the present paper we describe the Risk Assessment Analysis of Chemical, Biological, Radiological and Nuclear (CBRN) threat in the EU emphasised in South-east European countries. This paper draws upon material available in the public domain to address three questions: What are chemical, biological, radiological and nuclear weapons, and how available are they?; What could terrorists do with CBRN?, and Why and how serious is the danger overall? Nowadays, the most serious threats considered to be, firstly, the chemical and biological, and secondly the nuclear. The dissemination of CBRN as weapons of mass destructioon (WMD) is one of the most crucial issues of international security. The vivid effusion of this phenomenon in the region of Middle East and North Africa has possible consequences limited within the boundaries of this particular region. The terrorist organisations considered to be, by governments and the international community, a possible threat. In such a framework of the international environment, South-east European countries seems to live in. These countries, through their participation in international organisations exercise pressure for the termination, reduction and control of the accession of CBRN weapons. In this paper, are presented the most crucial proposals that could offer solutions to the present institutional framework which rules the risk assessment procedure on European, regional and national level.
Keywords: Chemical; Biological; Radiological nuclear threats; Assessment